Solving higher order Fuchs type differential systems avoiding the increase of the problem dimension - E. Navarro; L. Jódar; R. Company (International Journal of Mathematics and Mathematical Sciences)
In this paper, we develop a Frobenius matrix method for solving higher order systems of differential equations of the Fuchs type. Generalized power series solution of the problem are constructed without increasing the problem dimension. Solving appropriate algebraic matrix equations a closed form expression for the matrix coefficient of the series are found. By means of the concept of a k-fundamental set of solutions of the homogeneous problem an explicit solution of initial value problems are given.